The Dynamic Immunological Parameter Landscape in Coronavirus Disease 2019 Patients With Different Outcomes - Tang, Guoxing; Huang, Min; Luo, Ying; Liu, Wei; Lin, Qun; Mao, Liyan; Wu, Shiji; Xiong, Zhigang; Hou, Hongyan; Sun, Ziyong; Wang, Feng (Frontiers in Immunology, 2021)
Objectives: The longitudinal and systematic evaluation of immunity in Coronavirus Disease-2019 (COVID-19) patients were rarely reported. Methods: Parameters involved in innate, adaptive and humoral immunity were continuously monitored in COVID-19 patients from onset of illness until 45 days after symptom onset. Results: 27 mild, 47 severe, and 46 deceased COVID-19 patients were enrolled in this study. Generally, deceased patients demonstrated a gradual increase of neutrophils and IL-6 but decrease of lymphocytes and platelets after onset of illness. Specifically, sustained low numbers of CD8+ T cells, NK cells and dendritic cells were noted in deceased patients, while these cells gradually restored in mild and severe patients. Furthermore, deceased patients displayed a rapid increase of HLA-DR expression on CD4+ T cells in the early phase, but with low level of overall CD45RO and HLA-DR expressions on CD4+ and CD8+ T cells, respectively. Notably, in the early phase, deceased patients showed lower level of plasma cells and antigen-specific IgG, but higher expansion of CD16+CD14+ proinflammatory monocytes and HLA-DR-CD14+ monocytic-myeloid-derived suppressor cells (M-MDSCs) compared to mild or severe patients. Among these immunological parameters, M-MDSCs showed the best performance in predicting COVID-19 mortality, when using cutoff value of ≥ 10%. Cluster analysis found typical immunological pattern in deceased patients on day 9 after onset, which was characterized as the increase of inflammatory markers (M-MDSCs, neutrophils, CD16+CD14+ monocytes, and IL-6) but decrease of host immunity markers. Conclusions: this study systemically characterizes the kinetics of immunity of COVID-19, highlighting the importance of immunity in patient prognosis.